2005
DOI: 10.1080/03079450500096539
|View full text |Cite
|
Sign up to set email alerts
|

S1 gene characteristics and efficacy of vaccination against infectious bronchitis virus field isolates from the United States and Israel (1996 to 2000)

Abstract: The S1 genes of isolates of avian coronavirus infectious bronchitis virus (IBV) from commercial chickens in the US and Israel (20 isolates from each country) were studied using reverse transcription-polymerase chain reaction restriction fragment length polymorphism and sequencing. Partial sequences spanning the amino terminus region of S1 from amino acid residues 48 to 219, based on the Beaudette strain, were used for analysis. Phylogenetic clustering and high-sequence identity values were used to identify iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
119
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 31 publications
5
119
1
Order By: Relevance
“…Extraction of IBV RNA, reverse transcriptase-polymerase chain reaction of S1 gene fragments and analysis of sequences were performed as described elsewhere (Gelb et al ., 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of IBV RNA, reverse transcriptase-polymerase chain reaction of S1 gene fragments and analysis of sequences were performed as described elsewhere (Gelb et al ., 2005).…”
Section: Methodsmentioning
confidence: 99%
“…However, different strains of IBV have been circulating in the Middle East. For example, IBV variants like Q1 (CK/CH/LDL97I/97) (1,11,14,17,20,26,27), IBV variant-1 (793/B, IS/222/96, IS/251/ 96, and IS/64714/96), IBV variant-2 (IS/223/96, IS/572/98, IS/ 585/98, and IS/589/98), Egypt/Beni-Seuf/01, Sul/01/09, D274, and IS/885/00 as well as vaccine strains derived from Massachusetts and 4/91, (8,18,19,24,25) have been detected.…”
mentioning
confidence: 99%
“…Liu et al [15] and Gelb et al [7] reported the relationship between genotype and efficacy of a vaccine against field isolates and showed that vaccines with high S1 identity values are protective against field isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the use of vaccines for control of IB, the disease continues to be a problem in commercial poultry because IBV readily undergoes mutation in chickens and some serotypes do not cross-protect against antigenically unrelated serotypes, including new variant serotypes [7,12].…”
mentioning
confidence: 99%